Character Recognition - Mori, Minoru; Mori, Minoru (IntechOpen, 2010)
Character recognition is one of the pattern recognition technologies that are most widely used in practical applications. This book presents recent advances that are relevant to character recognition, from technical topics such as image processing, feature extraction or classification, to new applications including human-computer interfaces. The goal of this book is to provide a reference source for academic research and for professionals working in the character recognition field.
English
Keywords: Computer vision; Image processing